China’s National Digital Currency: An Overview of Digital Currency Electronic Payment - et. al., Xiang Zou, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Digital Currency Electronic Payment (DCEP) is the Central Bank Digital Currency (CBDC) of China. It is significantly different from electronic currency and third-party payment instruments. DCEP is issued through the dual mode which consists of the central bank and commercial banks. It operates and circulates based on the framework of Digital Currency Registration Center, Identity Authentication Center and Big Data Analysis Center. Compared with the encrypted digital currency based on blockchain technology, DCEP has the characteristics of centralized management. DCEP will have profound impacts on the effectiveness of monetary policy, the operation of banks and payment institutions, the development of digital economy, the internationalization of CNY and even social governance.